2011
DOI: 10.1080/02640414.2011.587445
|View full text |Cite
|
Sign up to set email alerts
|

Movement and physiological match demands of elite rugby league using portable global positioning systems

Abstract: Twelve elite players from an English Super League club consented to participate in the present study using portable global positioning system (GPS) devices to assess position-specific demands. Distances covered at low-intensity running, moderate-intensity running, high-intensity running, very high-intensity running, and total distance were significantly (P < 0.05) lower in forwards compared with outside backs and adjustables. Metres per minute was higher in adjustables and forwards, owing to higher values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
129
4
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(141 citation statements)
references
References 26 publications
4
129
4
4
Order By: Relevance
“…Alternatively, the maintenance of peak force may be due to a greater involvement of the lower body in high velocity movements as opposed to high force movements during competition (21,22,43). These findings suggest that rugby league competition compromises the velocity of lower body movements rather than the ability to generate force.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Alternatively, the maintenance of peak force may be due to a greater involvement of the lower body in high velocity movements as opposed to high force movements during competition (21,22,43). These findings suggest that rugby league competition compromises the velocity of lower body movements rather than the ability to generate force.…”
Section: Discussionmentioning
confidence: 94%
“…Depending on playing position, players cover distances in the range of 3,000-8,000 m during a match (27,33,43). Over the course of a rugby league season, players are required to compete on a weekly basis over a 7-8 month period, with generally 5-10 days between matches.…”
Section: Introductionmentioning
confidence: 99%
“…Highton, Worsfold, & Daniels, 2011a) and has tended to focus on established ESL teams 55 competing at the top of the table (Twist et al, 2014;Waldron et al, 2011a). Previous 56 research in the NRL has found that the physical demands are greater when competing 57 against bottom four ranked teams (Gabbett, 2013) and also the amount of HSR has 58 previously been used to differentiate between standards of competition (Gabbett, 2014).…”
mentioning
confidence: 99%
“…Adult rugby league involves prolonged periods of low-to-moderate intensity movement, interspersed by multiple sprints and contacts with the opposition (18,38,48). Adolescent youth players perform a similar pattern of activities during a match, with a notable 10-min annual increase in match duration.…”
mentioning
confidence: 99%